Effect of aspect ratio on thermal conductivity of high density polyethylene/multi-walled carbon nanotubes nanocomposites. (March 2016) - Evgin, Tuba; Koca, Halil Dogacan; Horny, Nicolas; Turgut, Alpaslan; Tavman, Ismail Hakkı; Chirtoc, Mihai; Omastová, Maria; Novak, Igor
Abstract: This study aims to investigate experimentally the effects of aspect ratio (length/diameter ratio) and concentration of multiwalled carbon nanotubes (MWCNTs) on thermal properties of high density polyethylene (HDPE) based composites. The aspect ratios of two types of MWCNT fillers are in the range of 200–400 and 500–3000. Composite samples were prepared by melt mixing up to weight fraction of 19% filler content, followed by a compression molding. Measurements of density, specific heat and thermal diffusivity (by modulated photothermal radiometry, PTR) were performed and effective thermal conductivities ke of nanocomposites were calculated using these values. The results show that the composites containing MWCNTs with higher aspect ratio have higher thermal conductivities than the ones with lower aspect ratio. In terms of conductivity enhancement ke / km − 1, the results indicate that MWCNTs with higher aspect ratio provide three to fourfold larger enhancement than the ones with lower aspect ratio, at low filler concentrations.